Temporal performance of castor vis-à-vis competing crops in Gujarat - A Markov chain analysis: Temporal performance of castor vis-à-vis competing crops in Gujarat - A Markov chain analysis - C SARADA,; S V RAMANA RAO, (Journal of Oilseeds Research, 2020)
Temporal performance of castor cultivation in Gujarat for the last five decades was studied. The study divided into five periods and transition probabilities were calculated for castor and its competing crops with respect to area and production. Results indicated that over all share of castor was very high with respect to area (84.8) and production (74.2). Castor share in area during Decade IV and V were low compared to previous periods. However, there was three-fold increase in production contribution in Decade V compared to the earlier period. This increase in production contribution despite of reduction of area retention can be attributed to the release of high yielding public sector hybrids, associated technologies and its large scale adoption by NARES during the last two decades.